2022
DOI: 10.1177/01455613221078182
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor-Related Lifestyle Habits of Patients With Laryngopharyngeal Reflux

Abstract: Objective The role of lifestyle habits in patients with laryngopharyngeal reflux disease (LPRD) is comparatively underexplored. We aim to examine the specific lifestyle habits in patients with LPRD. METHODS Systematic sampling was applied to select respondents aged 18 through 80 years in otorhinolaryngology-head and neck surgery (OHNS) clinics in Nan Fang Hospital during August 2017–July 2018, 1658 eligible participants were included by a systematic sampling method. Subjects with RSI score>13 were considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…Our study results indicated that 30 (14.3%) adolescents were overweight, 1 (0.5%) adolescent had obesity, and no significant association was found between BMI and LPR incidence (p = 0.094). Our study results differ from those of the study of Wang et al (10) showing that subjects with BMI >25 kg/m 2 had a 0.61-fold LPR risk than had subjects with BMI ≤ 20 kg/m 2 (OR= 0.61; 95% CI 0.39 -0.95, p = 0.054). Obesity is known to be related to gastroesophageal reflux disease, in that visceral fat synthesizes various cytokines that may lead to esophageal inflammation and damage to the esophageal mucosal barrier through refluxindependent mechanisms, such that the esophageal mucosa becomes particularly susceptible to GERD-induced injury.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our study results indicated that 30 (14.3%) adolescents were overweight, 1 (0.5%) adolescent had obesity, and no significant association was found between BMI and LPR incidence (p = 0.094). Our study results differ from those of the study of Wang et al (10) showing that subjects with BMI >25 kg/m 2 had a 0.61-fold LPR risk than had subjects with BMI ≤ 20 kg/m 2 (OR= 0.61; 95% CI 0.39 -0.95, p = 0.054). Obesity is known to be related to gastroesophageal reflux disease, in that visceral fat synthesizes various cytokines that may lead to esophageal inflammation and damage to the esophageal mucosal barrier through refluxindependent mechanisms, such that the esophageal mucosa becomes particularly susceptible to GERD-induced injury.…”
Section: Discussioncontrasting
confidence: 99%
“…(29) However, in this respect the results of LPR studies are conflicting. (6,10) Our study results showed statistically significant differences in free sugars consumption between the LPR negative and positive groups (p< 0.049). Our results are identical to those of the study of Li et al (5) where free sugars consumption significantly increased the risk of LPR 1.656 times after adjustment for multiple covariates (AOR =1.656; 95%CI = 2.516 -6.661, p=0.003).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In addition to pathological gastro-oesophageal or pharyngo-laryngeal conditions which may be associated or non-recognised, several other risk factors related to GERD and LPRD may play a key role in favouring chronic-recurrent clinical courses, even in case of thorough diagnostic approaches and adequate treatment regimens. These risk factors include: inadequate dietary regimens (lack of adherence to the Mediterranean diet); high consumption of specific foods (acid or with high protein or fat content); poor eating habits; tobacco smoke; alcohol abuse; obesity and overweight; sleep disorders; psychosocial distress 98 .…”
Section: Failure and Relapses Of Laryngopharyngeal Refluxmentioning
confidence: 99%
“…The food frequency questionnaire is commonly used to assess dietary habits in clinical studies and it estimates the frequency of consumption of beverages and foods ( 11 , 12 ). Lifestyle habits, including eating habits, vary in different countries and are often culturally conditioned ( 13 , 14 ). Therefore, eating habits should be studied separately for each region.…”
Section: Introductionmentioning
confidence: 99%